Strategi Pengembangan Peserta Didik Perempuan Melalui Ekstrakurikuler di Madrasah Aliyah - Muhammad Nur Hakim; Aprilia Dewi Mahmudati (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2024)
The purpose of this study was to find out the management of coaching and development of students through extracurricular programs, which are based on the planning and implementation carried out by institutions at the MA Perguruan Mu'allimat Jombang. This study used a qualitative approach with a descriptive research type. The subjects in this study were the Head of Madrasah, Deputy Student Affairs, Student Unit Advisors and Extracurricular Trainers. The data collection techniques used in the form of observation, interviews and documentation. Data validity was tested by source and technique triangulation. The results of the research data obtained through reduced analysis are then presented and verified. The results of this study indicate that 1) extracurricular program development and development planning is carried out by analyzing needs, determining the types of activities and preparing programs 2) implementing extracurricular program coaching and development needs to carry out plans, implement policies, fulfill facilities and infrastructure and implement activities.